Využití finanční analýzy v podniku - Šafaříková, Sandra (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Bakalářská práce se zabývá využitím finanční analýzy v podniku RENVODIN – ŠAFAŘÍK, spol. s r.o. Teoretická část se zabývá využitím finanční analýzy, technik a metodických nástrojů, ukazatelů a dalších složek, které tvoří východisko pro praktickou část. Praktická část je zaměřena na stručnou charakteristiku podniku a na samostatné metody zhodnocení finančního zdraví. Závěrečná část obsahuje doporučené návrhy na zlepšení současného stavu.

The bachelor thesis focuses on the exploitation of a financial analysis in the company RENVODIN - ŠAFAŘÍK, s.r.o. The theoretical part describes the exploitation of the financial analysis, techniques and methodical tools, indicators and further components which comprise the background for the practical part. The practical part is focused on a brief characterization of the company and independent methods assessing the financial health. The final part contains recommendations on how to improve the status quo.
Applying Financial Analysis at a Company
Keywords: Finanční analýza; finanční zdraví; likvidita; rentabilita; výkaz zisků a ztrát; rozvaha; peněžní tok.; Financal analysis; financial health; liquidity; profitability; income statement; balance sheet; cash flow.